DEVELOPMENT OF RAINBOW MATRIX MANIPULATIVE LEARNING MEDIA ON MATERIAL OF DETERMINANTS AND MATRIX MULTIPLICATION - Arifin, Zainul; Hidayah, Indriati Nurul; Muksar, Makbul (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study aims to develop learning media with a visual manipulative approach from rainbow materials in matrix learning so that it can increase the effectiveness of mathematics learning with the use of learning media as one approach that has been proven effective in supporting student understanding. This study is included in research and development using the ADDIE development model. The stages in the ADDIE development model include Analysis, Design, Development, Implementation, and Evaluation. The subjects for observation and testing in this study were all female students of grade XI-9 of SMA Al Hikmah Surabaya. The instruments used were expert validation sheets, interviews, questionnaires, and observations. Data from these instruments were analyzed using a one-shot case study pattern. The results of the study indicate that the rainbow matrix learning media is valid, practical, and effective for use in mathematics learning in SMA Al Hikmah Surabaya class XI on the material of determinants and matrix multiplication.